INSTRUMEN ASESMEN BAGI PESERTA DIDIK DALAM PROSES PEMBELAJARAN BIOLOGI BERBASIS PBL (PROBLEM BASED LEARNING) - Aprianiwati, Rika; Susanti, Try; Nuraida, Nining (Jurnal BIOEDUIN, 2021)
This study aims produce assessment instruments for students in the process of biology learning based on PBL (Problem Based Learning) model. The resulting instrument is an assessment instrument of student affective domain. This research type is instrument development research using ADDIE model. Testing methods there are two stages of expert validation and testing conducted to determine the level of feasibility of the instrument. The validator is an evaluation expert, strategy expert, and language expert to assess the product through a validation questionnaire. While the trials have small group try-outs and field try-outs conducted to strengthen the feasibility of instruments that have been validated by experts. Implementation of the instrument is performed to determine the effectiveness and practicality of the instrument through questionnaires when used by teachers. Expert validation and test results on the instrument are highly feasible to use and the result of the implementation of the instrument is very practical and very effective.